Investigating the Students' Errors When Solving Analytical Mechanics Using Newman’s Error Analysis - Wafiq Mujahidul Haqq; Pratama, Rodeo Bagus; Farkhan, Muhamad Mi'da; Setiaji, Bayu (Impulse: Journal of Research and Innovation in Physics Education, 2021)
One of the problems in learning is the appearance of errors. These errors are clasified into five parts considering Newman’s Error Analysis. The purpose of this research is to analyze the errors in analytical mechanics using Newman's Error Analysis (NEA) prior to the construction of the future effective and efficient learning. This research is using descriptive and qualitative research with test and interview. Based on the analysis, in analytical mechanics class, the students’ performance is low. From the Newman’s Error Analysis (NEA), we found the errors are belong to the several categories of NEA. In the whole aspect, the errors done by the students are correspond to the five aspects of Newman’s Error Analysis (NEA) which are connected to each other aspects. One can also note, the students’ performance in analytical mechanics class is low.